Structural Insights for Core Scaffold and Substrate Specificity of B1, B2, and B3 Metallo-β-Lactamases - Yun, Yeongjin; Han, Sangjun; Park, Yoon Sik; Park, Hyunjae; Kim, Dogyeong; Kim, Yeseul; Kwon, Yongdae; Kim, Sumin; Lee, Jung Hun; Jeon, Jeong Ho; Lee, Sang Hee; Kang, Lin-Woo (Frontiers in Microbiology, 2022)
Metallo-β-lactamases (MBLs) hydrolyze almost all β-lactam antibiotics, including penicillins, cephalosporins, and carbapenems; however, no effective inhibitors are currently clinically available. MBLs are classified into three subclasses: B1, B2, and B3. Although the amino acid sequences of MBLs are varied, their overall scaffold is well conserved. In this study, we systematically studied the primary sequences and crystal structures of all subclasses of MBLs, especially the core scaffold, the zinc-coordinating residues in the active site, and the substrate-binding pocket. We presented the conserved structural features of MBLs in the same subclass and the characteristics of MBLs of each subclass. The catalytic zinc ions are bound with four loops from the two central β-sheets in the conserved αβ/βα sandwich fold of MBLs. The three external loops cover the zinc site(s) from the outside and simultaneously form a substrate-binding pocket. In the overall structure, B1 and B2 MBLs are more closely related to each other than they are to B3 MBLs. However, B1 and B3 MBLs have two zinc ions in the active site, while B2 MBLs have one. The substrate-binding pocket is different among all three subclasses, which is especially important for substrate specificity and drug resistance. Thus far, various classes of β-lactam antibiotics have been developed to have modified ring structures and substituted R groups. Currently available structures of β-lactam-bound MBLs show that the binding of β-lactams is well conserved according to the overall chemical structure in the substrate-binding pocket. Besides β-lactam substrates, B1 and cross-class MBL inhibitors also have distinguished differences in the chemical structure, which fit well to the substrate-binding pocket of MBLs within their inhibitory spectrum. The systematic structural comparison among B1, B2, and B3 MBLs provides in-depth insight into their substrate specificity, which will be useful for developing a clinical inhibitor targeting MBLs.